Identification of Staphylococcus species and subspecies by the chaperonin 60 gene identification method and reverse checkerboard hybridization. - Goh, S H (1997)
A previous study (S. H. Goh et al., J. Clin. Microbiol. 34:818-823, 1996) demonstrated that a 600-bp region of the chaperonin 60 (Cpn60) genes from various bacterial isolates could be amplified by PCR with a pair of degenerate primers and that the products could be used as species-specific probes for Staphylococcus aureus, S. epidermidis, S. haemolyticus, S. lugdunensis, S. saprophyticus, and S. schleiferi. To further validate the utility of bacterial Cpn60 genes as universal targets for bacterial identification (ID), reverse checkerboard chemiluminescent hybridization experiments were performed with DNA probes from 34 different Staphylococcus species and subspecies. With the exception of probes from the Cpn60 genes of S. intermedius and S. delphini, which cross hybridized, all were species specific. Two subspecies of both S. capitis and S. cohnii were differentiated from one another, while DNAs from the two S. schleiferi subspecies cross hybridized. When 40 known Staphylococcus isolates were tested in a blind experiment by the Cpn60 gene method, 36 strains, representing six species and one subspecies (S. sciuri, S. caseolyticus, S. hominis, S. warneri, S. hyicus, S. haemolyticus, and S. capitis subsp. ureolyticus), were correctly identified. DNA from the four remaining isolates, known to be S. hyicus bovine strains, failed to hybridize to DNA from the S. hyicus target strain or any other Staphylococcus species. However, DNAs from these S. hyicus isolates did cross hybridize with each other. New DNA sequence data and evidence from previous studies suggest some genetic divergence between the two groups of S. hyicus isolates. Our results demonstrate that this Cpn60 gene-based ID method has the potential to be a basic method for bacterial ID. Studies are in progress to further validate the utility of this Cpn60 gene system for ID of Staphylococcus and other genera, including those of slow-growing microorganisms.